2021
DOI: 10.1002/nop2.979
|View full text |Cite
|
Sign up to set email alerts
|

When breaking the rule becomes necessary: The impact of leader–member exchange quality on nurses pro‐social rule‐breaking

Abstract: Aim Despite the literature on nursing leadership, the research on the quality of exchange relationship between nursing leaders and nurses is in its initial stages. Also, the underlying mechanism that exists between leader–member exchange and employee outcomes warrants further inquiry. This study aimed to fill these gaps by investigating the role of leader–member exchange relationships and organizational identification in nurses' intentional violation of hospital regulations to promote their patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 119 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…All measures were in English as this is the official language of Pakistan and used the medium for conveying the knowledge in schools and universities. Previous studies have also used English for conducting surveys and administering questionnaires ( Um-e-Rubbab and Naqvi, 2020 ; Irshad et al, 2021a ; Majeed et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…All measures were in English as this is the official language of Pakistan and used the medium for conveying the knowledge in schools and universities. Previous studies have also used English for conducting surveys and administering questionnaires ( Um-e-Rubbab and Naqvi, 2020 ; Irshad et al, 2021a ; Majeed et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The response rate turned out to be 50.8%. Other time lag studies have also faced the drop out of response rate [46][47][48][49]. One of the significant reasons behind a lower response rate is the tough schedule and workload of the healthcare workers due to a continuous increase in COVID-19 patients.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…For instance, in a study based on samples from diverse Chinese sectors, Zhu et al (2018) found that PSRB norms mediated the association between ethical leadership and PSRB. Similarly, a study found that organizational identification mediated the association between LMX quality and PSRB (Irshad et al, 2022). In addition, Potipiroon (2022) found that red tape mediated the association between formalization and PSRB.…”
Section: Mediatorsmentioning
confidence: 91%